Editor's Note = Note de directeur [40, Fall 1997] - Kealey, Gregory S.; Palmer, Bryan D. (Labour/Le Travail, 1997)
Bryan Palmer is succeeding Gregory Kealey, who is stepping down as editor after 21 years. Mark Leier is succeeding Palmer as the book review editor; Palmer had held the post for nearly 15 years. In turn, Andrew Parnaby and Richard Rennie are the new co-editors of the Notebook, succeeding Leier. Andrée Lévesque continues as the French book review editor. Various editorial board changes are noted. As incoming editor, Palmer offers a reflection on the journal and its path forward.
Keywords: Editors; Labor; Retirement